Examining gender differences in reactive aggression after transcranial direct current stimulation - Ye, Chelsea Kai Qi (Nanyang Technological University, 2020)
The ventromedial prefrontal cortex (VMPFC) has been empirically linked to aggressive behaviour, yet the causal role of this brain region in aggression remains to be fully understood. This study investigates the effects of stimulating the VMPFC through transcranial direct current stimulation (tDCS) on reactive aggression and tests whether there are gender differences in the effectiveness of tDCS in lowering reactive aggression. Some studies have found that the administration of tDCS to various brain regions to be effective in reducing aggression levels. Hence, it was hypothesized that there would be significant effects of tDCS on aggression. It was also hypothesized that males would have greater reductions in aggression following tDCS. In this double-blind, placebo-controlled, randomized study, healthy undergraduate students (N = 32) underwent three consecutive sessions of either tDCS or sham stimulation. Reactive aggression was evaluated post-stimulation using a well-validated laboratory measure, the Point Subtraction Aggression Paradigm. No significant effects of tDCS on aggression were observed and there were no gender differences in the effectiveness of tDCS in reducing aggression. The null findings are at odds with some previous studies, and possible reasons for this are discussed. Nonetheless, results were in the direction hypothesized. Future research can consider alternative tDCS protocols and extending to populations where aggression is more prevalent such as violent offenders. The findings extend the current limited literature on tDCS and aggression, which can have important implications for gender-specific responses to interventions for aggression.